ANALISIS MINAT DAN KEPUTUSAN PEMBELIAN MELALUI HARGA, KUALITAS DAN INOVASI - Saputro, Samuel Henry; Widyastuti, Maria (UNIKA Santo Thomas, 2022)
The development of communication technology causes smartphones to dominate the market, especially Chinese smartphone products. The number of Chinese products in the market is due to cheap and affordable prices, but not accompanied by good quality so that the Indonesian people already have their own views on Chinese products. However, Xiaomi as one of the mobile phone manufacturers from China in fact managed to become one of the kings of the smartphone market in Indonesia, this is because the price is affordable. This study aims to analyze interest and purchase decisions through price, quality and innovation. The results of data processing proved that all statement items were valid and all variables were reliable. The results showed that interest and purchasing decisions for Xiaomi smartphones in East Surabaya through price, quality and innovation were said to be moderate. Subsequent results show consumer interest and purchase decisions due to price and product quality, while innovation is not the cause of interest and purchase decisions for Xiaomi smartphones in East Surabaya, but purchasing decisions are due to price and product quality through interest first